Persepsi Pedagang di Kecamatan Lima Kaum terhadap Berzakat Melalui BAZNAS Kabupaten Tanah Datar - Widi Nopiardo (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research discusses the perceptions of traders in Lima Kaum District regarding zakat through BAZNAS Tanah Datar Regency. There is still a minimal amount of zakat coming from traders to BAZNAS Tanah Datar Regency, even though the trade sector is growing. This type of research is field research with a qualitative approach. Data collection techniques through interviews and documentation. Data analysis techniques through data reduction, data presentation, and drawing conclusions. Techniques for guaranteeing data validity through triangulation. The results of the research show that the majority of traders with muzaki status have a positive and good perception of BAZNAS Tanah Datar Regency because of its existence in Tanah Datar in helping mustahik. However, when their assets reached the provisions for zakat, some of them still had not paid their zakat through BAZNAS Tanah Datar Regency, they handed over their zakat themselves to the mustahik for various reasons. Meanwhile, a small number of others have submitted their zakat through BAZNAS Tanah Datar Regency.